Power Cycling Capability and Reliability Test of IGBT Modules - LI Shiping; HUANG Rong; FENG Qin; WAN Chaoqun; CHEN Yan (机车电传动)
In order to examine the reliability of IGBT modules , IGBT package structure was analyzed and a new model of powercycling was proposed based on the traditional method. Tests were performed on IGBT modules by power cycling and the failed situationwas shown. Compared to traditional life prediction and reliability evaluation of IGBT, the new power cycling method proposed in thispaper is more closer to the actual application and also more useful to IGBT failure analysis.